A Defensive "stand-by reaction" at Critical Moments of the Reproductive Life Cycle - Justo, João (2014)
Investigation about the psychological experiences of the reproductive life cycle showed that in critical moments special reactions may happen. These reactions seem to be defensive in nature, are set in motion in order to promote some kind of emotional protection and are performed in two opposite directions: a) a decreasing of the contact with aggressive impulses and b) an increasing of the use of rationalization and denial of frustrating situations. Examples of those rearrangements were observed at samples of: 1) pregnant women in obstetric high-risk consultation, 2) infertile couples waiting for infertility consultations and 3) pregnant women waiting for amniocentesis results. These data seem to be in accordance with the classical psychological points of view: a) gestation should be considered as a period of protection, b) during pregnancy a “primary maternal preoccupation” (Winnicot, 1958) emerges leading to the mobilization of all resources available for pregnant women and c) along gestational development psychological changes show how flexible maternal functioning may become. What was not expected is that in the absence of pregnancy, infertile couples should behave very similarly to what it is observed when pregnancy is in danger or when medical problems about the mother’s or the baby’s health arise in the horizon. Due to its “freezing” consequences upon emotional development we propose that this kind of reaction will be designated as “stand-by reaction”.